Perancangan Interior Dog Shelter dan Café di Surabaya - Deviani, Angelia (Intra, 2017)
In the city of Surabaya there are still many people who do not care about the abandoned dogs, one of the reasons for not helping abandoned dogs is the absence of space at home to provide temporary shelter. In the other hand, some people also use religious beliefs as an excuse. Based on those phenomenon,the author  then  designed a shelter and café where not only to accommodate abandoned animals but also find the owner for the dog. So the café is designed to be useful as a gathering place for animal lovers and provide campaigns to adopt dogs. In this design there are also supporting facilities such as clinic, nursery, playgrounds and office to organize dog adoption procedures. To create the design of the shelter and cafe, the author uses the method of design thinking.